Wireless VPN network structure and safety protection in the north and south call center of SGCC - Ying ZOU; Yirong WANG; Yanru WANG; Sining WANG (Dianxin kexue)
The wireless virtual private network structure suitable for the north and south call center of SGCC was explored. In the structure，the wireless applications and communication of the north and south call center of SGCC were considered. The existing access security risks and the cannot-control defects of wireless virtual private network were analyzed，and the solutions for the center were given. Through the research on wireless virtual private network security from the four aspects as the terminal，network，boundary and application，reference for the design and construction of the center wireless virtual private network was provided.